Unraveling immunosenescence in sepsis: from cellular mechanisms to therapeutics - Yanghanzhao Wang; Hao Zhang; Changhong Miao (Cell Death and Disease)
Abstract Sepsis is a life-threatening multiple organ dysfunction resulting from a dysregulated host response to infection, and patients with sepsis always exhibit a state of immune disorder characterized by both overwhelming inflammation and immunosuppression. The aging of immune system, namely “immunosenescence”, has been reported to be correlated with high morbidity and mortality in elderly patients with sepsis. Initially, immunosenescence was considered as a range of age-related alterations in the immune system. However, increasing evidence has proven that persistent inflammation or even a short-term inflammatory challenge during sepsis could trigger accelerated aging of immune cells, which might further exacerbate inflammatory cytokine storm and promote the shift towards immunosuppression. Thus, premature immunosenescence is found in young sepsis individuals, which further aggravates immune disorders and induces the progression of sepsis. Furthermore, in old sepsis patients, the synergistic effects of both sepsis and aging may cause immunosenescence-associated alterations more significantly, resulting in more severe immune dysfunction and a worse prognosis. Therefore, it is necessary to explore the potential therapeutic strategies targeting immunosenescence during sepsis.